1990
DOI: 10.1111/j.1600-0714.1990.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of AIDS in a heterosexual population in a Zaire hospital

Abstract: Oral lesions associated with HIV infection as classified by the WHO Collaborative Centre for Oral manifestation of HIV were studied in 83 heterosexual AIDS patients in Kinshasa, Zaire. One or more lesions were fungal (94%), bacterial (33%) and viral (23%). Neoplasm was found in 12% of cases while lesions of unknown etiology in 14%. As location of those lesions, the palate, lips, tongue and the buccal mucosae mostly predominate as sites. The findings from this study were clinically similar to those reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
51
2
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 16 publications
(7 reference statements)
12
51
2
6
Order By: Relevance
“…The most common oral lesion is oral candidiasis, with pseudomembranous type the most frequent 2,3,8 . Historically, this was one of the first documented oral features of AIDS and several studies have confirmed its high prevalence 9,10 . Oral lesions can appear at any stage of HIV infection with higher occurrence associated with increasing immunosuppression, and are more frequent in women than in men, and the most common pathogen is Candida albicans 8 .…”
Section: Introductionmentioning
confidence: 90%
“…The most common oral lesion is oral candidiasis, with pseudomembranous type the most frequent 2,3,8 . Historically, this was one of the first documented oral features of AIDS and several studies have confirmed its high prevalence 9,10 . Oral lesions can appear at any stage of HIV infection with higher occurrence associated with increasing immunosuppression, and are more frequent in women than in men, and the most common pathogen is Candida albicans 8 .…”
Section: Introductionmentioning
confidence: 90%
“…A comprehensive review of epidemiologic studies on HIV-related oral lesions reported from developed and developing countries over more than a decade, encompassing the pre-HAART and early-HAART period from 1986 to 2000, revealed oral candidiasis as the most common lesion found in all ages across the world (Patton et al, 2002). Prevalence of the lesion, however, ranged considerably from as low as 5% found in two separate studies in Minnesota (Little et al, 1994;Melnick et al, 1991) to as high as 94% among those with AIDSdefining illnesses in Zaire (Tukutuku et al, 1990). This review paper by Patton et al (2002), which was the outcome of an International Workshop that addressed the prevalence and classification of HIV/AIDS associated oral lesions, identified hairy leukoplakia as the second most reported oral lesion with prevalence that ranged from 2% in Nairobi, Kenya (Wanzala et al, 1989) to 43% in Mexico (Gillespie & Mariño, 1993).…”
Section: Epidemiology Of Hiv-associated Oral Manifestationsmentioning
confidence: 99%
“…Prevalence of other oral lesions commonly associated with HIV also varies according to region of the world and the population examined (Patton et al, 2002). According to the review by Patton et al (2002), Kaposi's sarcoma was reported to be present in 12% of 83 heterosexual AIDS patients in Kinshasa, Zaire (Tukutuku et al, 1990), while higher frequency of 38% was found among 84 AIDS patients in the United States (Roberts et al, 1988). HIV-related periodontal lesions, namely linear gingival erythema, necrotizing ulcerative gingivitis and necrotizing ulcerative periodontitis were found in up to 22% of patients in New York (Lamster et al, 1994), 24% in Argentina (Gillespie & Mariño, 1993), and 23% in India (Anil & Challacombe, 1997), respectively.…”
Section: Epidemiology Of Hiv-associated Oral Manifestationsmentioning
confidence: 99%
“…Incidence of oral candidiasis has been high in developing countries (Tukutuku, et al, 1990). Since the discovery of HIV in 1981, candidiasis has been shown to be associated with HIV-infected individuals (Gottlieb, et al, 1981).…”
Section: Introductionmentioning
confidence: 99%